2019
DOI: 10.12968/live.2019.24.4.183
|View full text |Cite
|
Sign up to set email alerts
|

The use of environmental enrichment on farms benefits animal welfare and productivity

Abstract: Environmental enrichment is a key aspect of animal welfare and productivity. Enrichment for livestock can be cost effective and used successfully on farm. The benefits generally outweigh any costs of providing enrichment and it should be taken into account when providing housing facilities for farm animals. It also reduces abnormal behaviours commonly seen in production animals, thus decreasing issues associated with poor animal health. The aim of this review is to summarise information and research that highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The benefits of using EE on land-farm animal welfare and productivity have been widely demonstrated, 11 but the EE needs of aquatic farmed animals have been largely overlooked. 6 The neglect of aquatic EE is mostly due to the debate on whether fish are sentient and capable of suffering (which now is clear), [12][13][14][15] as well as to the difficulty of observing aquatic animal behaviour in farming settings.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of using EE on land-farm animal welfare and productivity have been widely demonstrated, 11 but the EE needs of aquatic farmed animals have been largely overlooked. 6 The neglect of aquatic EE is mostly due to the debate on whether fish are sentient and capable of suffering (which now is clear), [12][13][14][15] as well as to the difficulty of observing aquatic animal behaviour in farming settings.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental enrichment, which involves providing biotic and abiotic stimuli in the environment, is a well‐established method for improving welfare (Bayne, 2018; Ellis, 2009; Makecha & Highfill, 2018). Research has shown that animals reared with environmental enrichment develop a more natural suite of behaviours (Ellis, 2009; Mason et al., 2007; Mkwanazi et al., 2019; Salvanes et al., 2013), experience reduced stress (Benaroya‐Milshtein et al., 2004; Crone et al., 2021; Godyń et al., 2019) and, interestingly, exhibit increased productivity (Bolt & George, 2019). This likely happens because enrichment provides an environment that is more similar to the natural one, which has shaped most of the evolutionary history of the species.…”
Section: Introductionmentioning
confidence: 99%
“…Animals 2024, 14, 1265 2 of 13 Environmental enrichment (EE) consists of enhancing animal's environment by modifying or adding items that encourage natural behaviors that can lead animals to experience positive emotional states [2,6]. Several studies have shown that EE improves the ability of domestic animals to cope with stress and can also be associated with preferences over certain objects [7,8].…”
Section: Introductionmentioning
confidence: 99%